Writing about Crime in Absentia: The Case of Sara Uribe’s Antígona González - Cantarello, Matteo (Confluenze. Rivista di Studi Iberoamericani, 2020)
This article analyzes the role of absence in Sara Uribe’s Antígona Gonzalez through the work’s construction of characters, portrayal of violence, and conceptualization of justice. By considering Antígona González as a “narconarrative”, this study illustrates how the work is innovative vis-à-vis most texts that stem from geographies and communities plagued by narcotraffic. Ultimately, this analysis examines how Antígona González engages in a dialogue with “narcoculture” and its glamorization by casting light on the often-ignored themes of absence and disappearance.